The Relationship Between Students' Reading Interest and Critical Reading Skills Among Eighth-Grade Students at SMP Negeri 5 Padangsidimpuan - Romaito, Efi Rilia Rizky; Siregar, Rini Kesuma; Ramadhani, Yulia Rizki (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2024)
This study explores the relationship between reading interest and critical reading skills among eighth-grade students at SMP Negeri 5 Padangsidimpuan. Utilizing a quantitative research approach, a twenty-item Reading Interest questionnaire and a critical reading skills test were administered to a sample of 30 students. The data collected were analyzed using statistical methods to determine the correlation between the two variables. The findings reveal a significant relationship between reading interest and critical reading skills, indicating that students with higher reading interest tend to exhibit better critical reading abilities. This suggests that fostering a strong interest in reading can enhance students' critical reading skills, making them more adept at analyzing, interpreting, and evaluating texts. The study highlights the importance of engaging teaching methods and diverse reading materials to boost students' interest in reading. Recommendations include the implementation of interactive learning strategies and the promotion of varied literary genres to support the development of students' critical reading skills. Future research should consider a larger sample and more comprehensive assessment tools to further explore these findings.